CLASSIFICATION OF INDICATORS OF INFORMATION SKILLS/ COMPETENCE OF PERSONALITY - Fedorov, О.В. (Journal of Information Technologies in Education (ITE), 2010)
The author has the conclusion that the information skills/competence of personality is the totality of the individual’s motives, knowledge, skills, and abilities (indicators: motivation, contact, content, perception, interpretation/appraisal, activity, and creativity) which promote to select, use, create, critically analyze, appraise, and transfer information messages and media texts in various forms and genres and to analyze the complex processes of functioning of information flows and media in society.